The Role of E-Budgeting in Mediating the Effect of Regional Budget Allocation on Poverty Reduction: Evidence from Tanjung Jabung Barat - Sawaluddin Fitri Tanjung; Syamsurijal Tan; Achmad Hizazi; Zamzami Zamzami (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Despite increasing APBD allocations in Tanjung Jabung Barat Regency, poverty reduction remains limited, suggesting that budget size alone is insufficient without effective governance tools. E-budgeting is proposed to enhance transparency, accountability, and effectiveness, although empirical evidence at the district level remains limited. Objective: This study analyzes the effect of APBD on poverty reduction, examines the mediating role of e-budgeting, and evaluates the APBD management strategy through SWOT analysis. Methods: A quantitative approach using PLS-SEM was employed with 25 purposively sampled OPDs involved in APBDplanning and poverty reduction programs. Data were collected through structured questionnaires using a 5-point Likert scale, while SWOT analysis was used to assess internal and external strategic factors. Results: APBD has no direct effect on poverty reduction, as indicated by the path coefficient of -0.036 and p-value of 0.776. However, its effect becomes significant when mediated by e-budgeting (APBD → e-budgeting = 0.667, p = 0.000; e-budgeting → poverty reduction = 0.673, p = 0.000), demonstrating the mediator’s role in improving transparency and effectiveness. The SWOT analysis shows that the APBD management strategy is favorable, as it leverages internal strengths and external opportunities. Conclusion: E-budgeting is essential for translating APBD allocations into effective poverty reduction. Strengthening digital governance and integrating e-budgeting with poverty monitoring systems are recommended.